Evaluation of Body Composition in Senegalese Patients with Chronic Respiratory Disease (International Journal of Physiology, 2024)
Background: Body composition could increase morbi-mortality occurrence risk of patients with chronic respiratory disease (CRD). In low income countries, this relation was less studied. Thus, our study aimed to evaluate the body composition in patients with CRD.Methodology: Study participants were asthmatic or chronic obstructive disease (COPD) patients. Anthropometric and body composition parameters were measured and classified by Schols et al. Spirometric parameters were measured according the ATS/ERS guidelines of 2005. Results: A total of 39 patients were recruited in our study (18 asthmatics and 21 COPD patients). All patients had muscle depletion.Fat free mass (FFM), fat free mass index (FFMI), skeletal muscle mass (SMM) and skeletal muscle mass index (SMMI)werelower in COPD patients. However, asthma patients were more obese while cachexia were more frequent inCOPD patients. Semistarvation were found in all patients with Gold stage III and to a lesser extent in some patient of Gold stage II and IV.FVC and FEV1, expressed on percentage of predicted value,were positively correlated with FFMI and SMMI in COPD patients.Conclusion: Our patients had mild to moderate forms of their disease and their body composition may increase severity of CRD.